Quantitative characterization and influencing factor analysis of coal structure of deep coal reservoirs in Linxing area - Xiangdong GAO; Shihao ZHOU; Hui GUO; Hao SUN; Mingda ZHANG; Chaowei LUO; Yanbin WANG; Xiang WU (Meitan kexue jishu)
The quantitative characterization of coal structure is one of the hot topics in coal reservoir research. To finely characterize the spatial distribution of coal structure and identify the main controlling factors for its differential distribution, through observation and measurement of coal cores, quantitative characterization of coal structure using geological intensity factors, and statistics of logging response of different coal structures, a quantitative characterization model of coal structure based on logging curves was constructed. The spatial distribution of coal structure was predicted, and the influence characteristics of sedimentation, structure, in-situ stress, and micro-mechanical properties on coal structure were explored. The research results indicate that density, gamma-ray, interval transit time, and caliper loggings are sensitive to the coal structure, and the use of logging multiple regression method can significantly improve the accuracy of coal structure identification. The coals in the study area are mainly composed of primary-fragmented coals, followed by cataclastic coals, with a small amount of primary and cataclastic-granulated coals developed. The coal structure of the entire study area can be divided into four categories and seven small areas. The sedimentary environment can affect the coal structure by controlling the thickness of coal seam development. The thickness of coal seams developed in tidal channels, sand flats, mud flats, delta plains, and lagoon environments gradually increases, but there is no obvious relationship between coal structure and coal seam thickness. However, the ash content is positively correlated with the integrity of coal structure, and studying the changes in ash content in different sedimentary environments is the key to revealing the control characteristics of sedimentary environments on coal structure. The average structural curvature of primary structured coals, primary- fragmented structured coals, and cataclastic coals are 8.4×10−6, 18.7×10−6, 25.7×10−6 m−1, respectively. Where faults develop, the coal structure is characterized by cataclastic coals. As the burial depth increases, the in-situ stress increases, and the integrity of the coal structures are enhanced. Based on this, the in-situ stress state further differentiates the coal structures. In the shallow extensional and compression transition zone, the coal structure is mainly fragmented and fragmented; In the deep compression state, the primary fragmented structure is dominant; The proportion of fractured structures in the deep compression and extension transition zone has increased. The micro mechanical properties of coal are controlled by the composition of coal matrix and micro pore structure. The mechanical strength of inorganic components of coal is higher than that of organic components of coal, and the pore size of inorganic components is smaller than that of organic components. The higher the content of inorganic components, the higher the mechanical strength of coal, and the more complete the coal structure. This research achievement provides reference for coal seam drilling construction, fracturing transformation, and reservoir evaluation.